Biohidrogenação microbiana e o fluxo duodenal de ácidos graxos do rumen em novilhos de corte suplementados com fontes lipídicas em dietas contendo glicerina - Gómez Insuasti, Arturo Samuel [UNESP] (2015)
Evaluations of this work were done in vivo and in vitro. The purpose of the in vivo study was to evaluate the effect of soybean oil sources in combination with glycerin in diets for ruminants in ruminal fermentation, microbial protein synthesis, ruminal efficiency and intestinal flow of fatty acids. Eight steers Nellore, with initial weight of 554.13 ± 36,35 kg and average age of 30 months, with ruminal and duodenal cannulas were fed diets containing glycerol (100 g/kg DM) and soybean oil sources ( 50 g/kg DM). Were provided four types of diets with proportion to forage:concentrate (30:70), corn silage was provided as roughage, and the concentrate was different soybean oil sources: 1) control diet CO; 2) diet with soybean GS; 3) diet with soybean oil OS; and 4) diet with commercial protected fat GP. The animals were divided into two Latin squares 4x4, with four experimental periods of 16 days each. Means were submitted to analysis of orthogonal contrasts. The use of soybean oil sources (5% EE) in combination with glycerin (100 g/kg DM) does not affect the consumption of MS, but the DM, FDNap and EE; not resulting in changes in rumen pH and concentrations of short-chain fatty acids. There was no reduction in the production acetate (65.63 Mm/L), but propionate production was increased (40.02 Mm/L) possibly due to the inclusion of glycerin, causing reduction in acetate: propionate ratio (1.69). The efficiency of microbial nitrogen synthesis was enhanced for diet OS (15.14 g N-Mc/kg MOAFR). Nitrogen retained in the tissue was greater in the diet SG (46.74%). The treatments affected the concentration and profile of fatty acids in the rumen and ruminal flow of fatty acids. The pass rate for linoleic acid was affected with the lowest value for OS and greater value for GS and GP; however, the biohydrogenation rate for linoleic and linolenic acid was higher for. The greater efficiency of the biohydrogenation of linoleic acid and oleic acid was to OS